Tourism on postage stamps in the Kingdom of Saudi Arabia | السياحة على الطوابع البريدية بالمملكة العربية السعودية - Yahya | يحي, Enas bint Fares | إيناس بنت فارس (2024)
A set of stamps was issued in 2004, bearing the phrase “Tourism in Saudi Arabia.” The Kingdom's interest in tourism began with the Seventh Development Plan after the directive to establish the Supreme Tourism Authority to develop the tourism sector. The Ninth Development Plan focused on tourism and devoted a separate chapter to it. It also pointed out its distinctive features, as it possesses 7,670 archaeological sites, 140 sites related to the history of the Kingdom of Saudi Arabia, 1,985 urban heritage sites, 287 handicraft sites, 479 desert historical sites, and 868 sites. Mountainous, and 74 historical marine sites. For this reason, the “Tourism in the Kingdom of Saudi Arabia” stamps for the year 2004 represented a major development. | صدرت مجموعة طوابع في عام 2004م، تحمل جملة "السياحة في السعودية". فقد بدأ اهتمام المملكة بالسياحة بدءًا من خطة التنمية السابعة بعد التوجيه بإنشاء الهيئة العليا للسياحة لتنمية قطاع السياحة. وركّزت خطة التنمية التاسعة على السياحة وأفردت لها فصلًا مستقلًا، كما أشارت إلى ما تتميز به من مقومات حيث تمتلك 7670 موقعًا أثريًا، و140 موقعًا يتعلّق بتاريخ المملكة العربية السعودية، و1985 موقعًا للتراث العمراني، و287 موقعًا للحرف اليدوية، و479 موقعًا تاريخيًا صحراوياً، و868 موقعًا جبليًا، و74 موقعًا بحريًا تاريخيًا لهذا السبب مثلّت طوابع "السياحة في المملكة العربية السعودية" لعام 2004م تطورًا كبيرًا.